2015
DOI: 10.1124/mol.114.096925
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Oligomeric Organization of the Human M3Muscarinic Acetylcholine Receptor

Abstract: G protein-coupled receptors, including the M 3 muscarinic acetylcholine receptor, can form homo-oligomers. However, the basis of these interactions and the overall organizational structure of such oligomers are poorly understood. Combinations of sitedirected mutagenesis and homogenous time-resolved fluorescence resonance energy transfer studies that assessed interactions between receptor protomers at the surface of transfected cells indicated important contributions of regions of transmembrane domains I, IV, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…For example, studies on the muscarinic M 2 receptor subtype have variously concluded that it may be predominantly monomeric but with a capacity to form dimers ( 4 ), is routinely dimeric ( 5 ), or is predominantly tetrameric ( 6 ). Similar variation has been reported for each of the muscarinic M 1 ( 5 , 7 ) and M 3 ( 8 11 ) subtypes. In addition, although certain studies have indicated that addition of muscarinic ligands does not affect the prevalence of receptor dimers/oligomers ( 5 , 12 ), other studies have indicated a capacity for regulation.…”
Section: Introductionsupporting
confidence: 81%
“…For example, studies on the muscarinic M 2 receptor subtype have variously concluded that it may be predominantly monomeric but with a capacity to form dimers ( 4 ), is routinely dimeric ( 5 ), or is predominantly tetrameric ( 6 ). Similar variation has been reported for each of the muscarinic M 1 ( 5 , 7 ) and M 3 ( 8 11 ) subtypes. In addition, although certain studies have indicated that addition of muscarinic ligands does not affect the prevalence of receptor dimers/oligomers ( 5 , 12 ), other studies have indicated a capacity for regulation.…”
Section: Introductionsupporting
confidence: 81%
“…Recently, mathematical analysis of spectrally resolved multi-photon FRET microscopy data has provided evidence that a substantial proportion of the human M 3 muscarinic acetylcholine receptor is present at the surface of transfected cells as a tetramer with rhombic organization ( 39 ). Moreover, as in-house data had shown a specific role for both TMD VII and TMD VI in organization of the tetramer via cholesterol molecules that bridge a pair (dimer + dimer) of TMD I-helix VIII interface M 3 muscarinic receptor dimers ( 40 ), we generated both additional mutants and models of potential organization of the hD 3 , akin to these muscarinic M 3 models, to explore if these could unify the experimental observations.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the observed proportions of receptor monomers, dimers and oligomers may well vary between individual cells and tissues and, furthermore, the binding of distinct ligand chemotypes may selectively alter this if they either differentially regulate receptor expression levels or stabilize distinct states of the receptor. Given roles of segments of the seven transmembrane domains (TMDs) of GPCRs that are located close to the extracellular face in controlling class A receptor dimerization 4, 20, 21 it is clearly possible that different antagonist/inverse agonist-bound structures of the same GPCR may alter the dimerization potential or propensity of the receptor and, therefore, the steady-state distribution of monomers, dimers and oligomers.…”
Section: Introductionmentioning
confidence: 99%